Water culture in Mexico and Costa Rica: a comparative study of their legislation - Ávila Verdín, Edgar Gabriel (2026)
Based on a qualitative theoretical research in which the Political Constitutions, secondarylaws, as well as specific regulations on the subject of Water Culture in Mexico and in CostaRica, including public policies, decrees, plans and projects, were reviewed, a comparativestudy was carried out, becoming the first experience in Latin America on the legal analysisthat regulates this fundamental element of water management. The main themes developedwithin each country are focused on: promoting the protection of this resource, sustainableuse, awareness, and sensitization of the population on the importance of water resources,through formal and non-formal education. As well, as the creation of strategies throughprograms or projects, which contribute to the generation of knowledge for informeddecision-making.